Retrospective audit compares screening and treatment of pregnancy-related anaemia in regional New South Wales with Australian guidelines - Mariam Ebrahim; Priya Dharshini Vadive; Tegan Dutton; Anayochukwu Edward Anyasodor; Uchechukwu Levi Osuagwu; Jannine Bailey (BMC, 2024)
Abstract Background Anaemia during pregnancy is common worldwide. In Australia, approximately 17% of non-pregnant women of reproductive age have anaemia, increasing to a rate of 25% in pregnant women. This study sought to determine the rate of screening for anaemia in pregnancy in regional New South Wales, and to determine whether screening and treatment protocols followed the recommended guidelines. Methods This retrospective study reviewed antenatal and postnatal (48 h) data of women (n = 150) who had a live birth at Bathurst Hospital between 01/01/2020 and 30/04/2020. Demographic data, risk factors for anaemia in pregnancy, antenatal bloods, treatments provided in trimesters one (T1), two (T2) and three (T3), and postpartum complications were recorded. These were compared to the Australian Red Cross Guidelines (ARCG) using descriptive statistics. Results Of the women with screening data available (n = 103), they were mostly aged 20-35yrs (79.6%), 23.3% were obese, 97.1% were iron deficient, 17% were anaemic and only a few (5.3%) completed the full pregnancy screening as recommended by the ARCG while a majority completed only partial screenings specifically Hb levels in T1 (56.7%), T2 (44.7%) and T3 (36.6%). Compliance to oral iron was largely undocumented, but constipation was a common side effect among the women. IV iron was administered in 14.0% of women, approximately 1.75x higher than the recommended rate. Conclusions This study provided useful information about compliance to screening and treatment guidelines for anaemia in pregnancy. We identified the need for improved documentation and communication between various health providers to ensure adequate antenatal care to prevent maternal complications during pregnancy. This will improve patient care and encourage further developments in maternal care, bridging the rural health gap.